2019
DOI: 10.5539/sar.v8n3p12
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Ammonia Volatilization from Waterlogged Acids Soils Using Organic Amendments

Abstract: In production agriculture, granular urea is the most used nitrogen fertilizer in crop production. However, increase in soil pH following application of urea causes ammonia volatilization and reduces N use efficiency. To minimize ammonia loss, organic amendments are used, however, type of organic amendment use could affect urea use efficiency. This study was to determine the effects of organic amendments derived from forest litter, Leucaena leucocephala, chicken litter, and cow dung on ammonia volatilization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The role of organic amendments like poultry manure, biochar, compost, etc. in mitigating NH 3 fluxes from wetland rice fields is unresolved since some researchers have reported positive effects (Saarnio et al, 2013;Malińska et al, 2014;Ali et al, 2019), while others reported negative effects (Feng et al, 2017;Chu et al, 2019;Rahaman et al, 2020). Ammonia emissions increase with the N fertilizer rate (Uddin et al, 2021;Jahangir et al, 2022) which suggests that with organic amendments the rate of N fertilizer application could be decreased to reduce both economic and environmental costs while maintaining soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…The role of organic amendments like poultry manure, biochar, compost, etc. in mitigating NH 3 fluxes from wetland rice fields is unresolved since some researchers have reported positive effects (Saarnio et al, 2013;Malińska et al, 2014;Ali et al, 2019), while others reported negative effects (Feng et al, 2017;Chu et al, 2019;Rahaman et al, 2020). Ammonia emissions increase with the N fertilizer rate (Uddin et al, 2021;Jahangir et al, 2022) which suggests that with organic amendments the rate of N fertilizer application could be decreased to reduce both economic and environmental costs while maintaining soil quality.…”
Section: Introductionmentioning
confidence: 99%